The influence of two variables of the nonlinear camera calibration on the 3D underwater accuracy - Bernardina, G. R. D.; Cerveri, P.; de Barros, R. M. L.; Silvatti, A. P. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to control two variables of the nonlinear camera calibration to evaluate if they affect the 3D undewater accuracy. Two cameras (GoPro, 60 Hz) were fixed in the swimming pool. In order to evaluate the influence of a distance constrain (1 and 2 markers) and the movement of the wand calibration, we performed three different movements: M1 (zig zag), M2 (circular) and M3 (up and down). In each condition the 3D accuracy were assessed in seven trials of a dynamic rigid bar test (ANOVA, p<0.05). The best accuracy results were found in the M1. In this movement the wand spread more the acquisition volume. No significant difference was found when we compare this movement using or not the distance constrain, however if the movement did not spread very well the volume the usages of the distance constrain improved significantly the results.